KOPERASI DAN BMT: SEBUAH FENOMENA SUMBER DANA UNTUK KEMASLAHATAN UMAT - Mikhriani, Mikhriani (Jurnal Dakwah, 2011)
In studying the structure of economy we always talk about Globalization, Capitalism and Socialism. Capital economic System and social economic system have negative effect to the Indonesian economic specially in the social effects. To eliminate the negative effect of capitalism economic System and socialism Economic System, Koperasi and BMT are the best ways of mechanism economic that can eliminate the negative effects of capitalism Economic System and socialism economic Economic System . Similarly with the Islam Economic System, Koperasi and BMT are positive way to make the condusif economic system. We all agree these Koperasi and BMT to be thebest funding system for entrepreneurship of Indonesian People. The values of Koperasi and BMT System is similarly with the ethics of Islam Economy System. Ethics in Islam is chiefly based on the Qur’an and Sunnah as the primary sources of Islamic jurisprudence, added by Ijma’ qiyas and followed by other secondary sources.